Insight into the role of grafting and arbuscular mycorrhiza on cadmium stress tolerance in tomato - Kumar, Pradeep; Lucini, Luigi; Rouphael, Youssef; Cardarelli, Mariateresa; Kalunke, Raviraj M.; Colla, Giuseppe (Frontiers in Plant Science, 2015)
Physiological, biochemical, metabolite changes and gene expression analysis of greenhouse tomato (Solanum lycopersicumL.) were investigated in two grafting combinations (self-grafted ‘Ikram’ and ‘Ikram’ grafted onto interspecific hybrid rootstock ‘Maxifort’), with and without arbuscular mycorrhizal (AM), exposed to 0 and 25 µM Cd. Tomato plants responded to moderate Cd concentration by decreasing yield and crop growth parameters due to the accumulation of Cd in leaf tissue, inhibition of the PS II activity, reduced nutrients translocation, and also to the oxidative stress as evidenced by enhanced hydrogen peroxide (H2O2) generation, ion leakage and lipid peroxidation. AM inoculation significantly enhanced the metal concentration in shoots and reduced growth and yield. The Ikram/Maxifort combination induced higher antioxidant enzymes, higher accumulation of proline and reduction of lipid peroxidation products. This suggests that the use of Maxifort rootstock in tomato has a high reactive oxygen species scavenging activity since lower H2O2 concentrations were observed in the presence of Cd. The higher crop performance of Ikram/Maxifort in comparison to Ikram/Ikram combination was also due to the improved nutritional status (higher P, K, Ca, Fe, Mn, and Zn) and increased availability of metabolites involved in cadmium tolerance (phytochelatin PC2 and fructans inulins). The up-regulation of LeNRAMP3 gene in leaf of Ikram/Maxifort could explain the better nutritional status of interspecific grafting combination (higher Fe, Mn, and Zn).